Involvement of the epidermal growth factor receptor in the modulation of multidrug resistance in human hepatocellular carcinoma cells in vitro - Hoffmann, Katrin; Xiao, Zhi; Franz, Clemens; Mohr, Elvira; Serba, Susanne; Büchler, Markus W.; Schemmer, Peter (Cancer cell international, 2011)
Hepatocellular carcinoma (HCC) is a molecular complex tumor with high intrinsic drug resistance. Recent evidence suggests an involvement of the tyrosine kinase pathway in the regulation of ATP-binding cassette protein (ABC-transport protein) mediated multidrug resistance in cancer cells. The aim of this study was to examine whether EGFR inhibition sensitizes HCCs to chemotherapy and to elucidate its mechanism.